A review of prospective pathways and impacts of COVID-19 on the accessibility, safety, quality, and affordability of essential medicines and vaccines for universal health coverage in Africa - Floriano Amimo; Ben Lambert; Anthony Magit; Masahiro Hashizume (BMC, 2021)
Abstract Background The ongoing pandemic of coronavirus disease 2019 (COVID-19) has the potential to reverse progress towards global targets. This study examines the risks that the COVID-19 pandemic poses to equitable access to essential medicines and vaccines (EMV) for universal health coverage in Africa. Methods We searched medical databases and grey literature up to 2 October 2020 for studies reporting data on prospective pathways and innovative strategies relevant for the assessment and management of the emerging risks in accessibility, safety, quality, and affordability of EMV in the context of the COVID-19 pandemic. We used the resulting pool of evidence to support our analysis and to draw policy recommendations to mitigate the emerging risks and improve preparedness for future crises. Results Of the 310 records screened, 134 were included in the analysis. We found that the disruption of the international system affects more immediately the capability of low- and middle-income countries to acquire the basket of EMV. The COVID-19 pandemic may facilitate dishonesty and fraud, increasing the propensity of patients to take substandard and falsified drugs. Strategic regional cooperation in the form of joint tenders and contract awarding, joint price negotiation and supplier selection, as well as joint market research, monitoring, and evaluation could improve the supply, affordability, quality, and safety of EMV. Sustainable health financing along with international technology transfer and substantial investment in research and development are needed to minimize the vulnerability of African countries arising from their dependence on imported EMV. To ensure equitable access, community-based strategies such as mobile clinics as well as fees exemptions for vulnerable and under-served segments of society might need to be considered. Strategies such as task delegation and telephone triage could help reduce physician workload. This coupled with payments of risk allowance to frontline healthcare workers and health-literate healthcare organization might improve the appropriate use of EMV. Conclusions Innovative and sustainable strategies informed by comparative risk assessment are increasingly needed to ensure that local economic, social, demographic, and epidemiological risks and potentials are accounted for in the national COVID-19 responses.